Trichoid sensilla on honey bee proboscises as inspiration for micro-viscometers. (1st January 2023) - Liao, Caiying; Amador, Guillermo J; Liu, Xuhan; Wu, Zhigang; Wu, Jianing
Abstract: Sensing physical properties of liquids, such as viscosity, is of great significance for both biological organisms and industrial applications. For terrestrial organisms feeding on liquids, such as honey bees that forage nectar, sensing viscosity may help to determine the quality of food sources. Previous experiments showed that honey bees exhibit strong preferences for less viscous nectar; however, the physical mechanism underlying how they perceive viscosity remains unexplored. In this study, we propose that the western honey bee ( Apis mellifera L.) is capable of distinguishing viscosity using the slender trichoid sensilla emerging from a ball and socket-like joint on the proboscis. Observations of the trichoid sensilla using transmission electron microscopy reveal physical characteristics that are typical of mechanosensory structures. Additionally, we found that bees actively alter the rate at which they feed based on the liquid's viscosity and not its sugar content, hinting at their sensing of viscosity. Through mathematical modeling, we found that the sensitivity of the biological viscometer was determined by its length, and the optimal sensitivity for a western honey bee occurs when the tongue interacts with nectar with a viscosity of 4.2 mPa·s, coinciding with the viscosities typically found in the wild. Our findings broaden insights into how honey bees adapt to varying-viscosity nectar from the perspective of mechanical sensing, and how the bee-flower partnership may be based around the optimal nectar viscosity for feeding. By understanding how bees may sense viscosity at the micrometer scale, we may motivate new technologies for micro-viscometers.